A modified and improved method to measure economy-wide carbon rebound effects based on the PDA-MMI approach. (December 2020) - Li, Ding; Gao, Ming; Hou, Wenxuan; Song, Malin; Chen, Jiandong
Abstract: Although energy technological progress has been regarded as an important driver for reducing carbon emissions, the existence of carbon rebound effect prevents a portion of the potential carbon reductions to be realized. Compared with the energy rebound effect, research on the carbon rebound effect is scarce because it is always equated with the energy rebound effect. However, the carbon rebound effect is more complex. Given that the traditional method for carbon rebound effect assessment only reflects energy rebound effects, our study proposed an improved production-theoretical decomposition analysis (PDA)-Meta-frontier Malmquist index (MMI)-based method and explored carbon rebound effects in China from 2006 to 2015. Our results show that (1) the eastern and western regions faced fewer carbon rebound effect risks compared with those of the central region due to decreasing emission intensity associated with energy technological progress; (2) the reductions in emission intensity in the eastern region relied both on coal and non-coal technology, whereas the western region only relied on coal technology; and (3) the non-coal technology in the eastern region was at the meta-frontier, whereas the non-coal technology of other regions exhibited catch-up effects. Highlights: We analyzed the carbon rebound effects (CRe) in China from 2006 to 2015. An improved PDA-MMI-based method for CRe assessment was proposed. The new method considers the effects of technology on emission intensity (CE). East and west China faced fewer CRe risks due to decreasing CE.